Diffusion-weighted perinatal postmortem magnetic resonance imaging as a marker of postmortem interval. - Arthurs, Owen J; Price, Gemma C; Carmichael, David W; Jones, Rod; Norman, Wendy; Taylor, Andrew M; Sebire, Neil J (European Radiology, 2015)
Objective: To evaluate perinatal body organ apparent diffusion coefficient (ADC) values at postmortem magnetic resonance imaging (PMMR) in order to evaluate postmortem changes.Methods: Postmortem diffusion-weighted imaging (DWI) of the thorax and abdomen were performed with diffusion gradient values b = 0, 500, and 1000 s/mm(2) on 15 foetal and childhood cases (mean 33.3 ± 7.8 weeks gestation) compared to 44 live infants (mean age 75.5 ± 53.4 days). Mean ADC values were calculated from regions of interest (ROIs) for the lungs, liver, spleen and renal cortex, compared to normative live infantile body ADC values of similar gestational age.Results: Mean ADC values were significantly lower in postmortem cases than in normal controls for liver (0.88 10(-3) mm(2)/s ± SD 0.39 vs. 1.13 ± 0.13; p < 0.05) and renal cortex (0.85 ± 0.26 vs. 1.19 ± 0.13; p < 0.05) but not spleen or muscle. Mean lung ADC values were significantly higher than normal controls (1.06 ± 0.18 vs. 0 ± 0; p < 0.001), and there was a significant correlation between postmortem interval and lung ADC (R(2) = 0.55).Conclusion: Lung PMMR ADC values are related to postmortem interval, making them a potential marker of time since death. Further research is needed to understand the organ-specific changes which occur in the postmortem period.Key Points: • Liver and spleen PM ADC values were lower than controls. • Lung ADC changes correlate with PM interval. • These findings may be useful in medicolegal cases.